Integration of Participatory Rural Appraisal in Resolution of Waste Management Policy Problems in Pariaman City - Mulyadi; Lince Magriasti (Alfuad: Jurnal Sosial Keagamaan, 2026)
Urban waste management is often trapped in a linear economic approach and top-down policy implementation, triggering social conflict and policy gaps at the local level. This study aims to analyze waste management issues in Pariaman City, specifically at the South Tungkal Landfill, which operates as an open dumping site, and to model problem-solving through Participatory Rural Appraisal (PRA) interventions. Using qualitative methods with a case study design, data were collected through in-depth interviews, observations, Focus Group Discussions (FGDs), and PRA instruments with 46 purposive informants from the government, affected communities, and waste bank managers. The results of the study indicate that waste management policy implementation in Pariaman City falls within the symbolic implementation quadrant (high ambiguity, high conflict), characterized by weak enforcement and community resistance. Through the application of PRA techniques (transect walk, matrix ranking, and social mapping), participatory mapping has proven effective in aligning priorities between the government and the community. This intervention shifts the implementation model toward experimental implementation, which encourages collaborative governance. In conclusion, institutionalizing PRA within the regional policy cycle is an absolute prerequisite for reducing conflict and building adaptive waste management.